A Comparative Evaluation of the Efficacy of Two Novel Desensitising Dentifrices. (6th December 2012) - Barlow, Ashley P.; He, Jane; Tian, Cindy; Jeffery, Peter; Mason, Stephen C.; Tai, Bao-Jun; Jiang, Han; Rees, Gareth D.; Du, Min Quan
Abstract : A comparison of the desensitising efficacy of two commercially available dentifrices with different modes of action was conducted in a randomised, examiner-blind, two-arm, parallel group, 8-week, longitudinal clinical study. Dentifrice A, (Sensodyne Multi Action Iso-Active), contained 50000 ppm KNO3 and 1450 ppm fluoride as NaF. Dentifrice B, Colgate Sensitive Pro-Relief, contained a combination of 80000 ppm arginine, bicarbonate, calcium carbonate, and 1450 ppm fluorine as NaMFP. Subjects (N = 110 ), stratified into two groups (N = 55 ), brushed twice-daily for 60 s, over an 8-week period. Sensitivity status, compliance, and safety were determined at 1, 2, 4, and 8 weeks. A fixed-effects ANCOVA statistical model was applied to the Intent-To-Treat population using a two-sided 5% significance level. After 8 weeks, the treatment groups using Dentifrice A and Dentifrice B exhibited mean reductions from baseline of 49% and 45% in air sensitivity visual analogue scale (VAS) score, 61% (both) in examiner-based Schiff Sensitivity score, and clinically significant reductions in tactile pain threshold; all reductions were statistically significant (P < 0.0001 ). Both treatment groups also exhibited significant reductions across all sensitivity measures at 1, 2, and 4 weeks (P ≤ 0.0059, Dentifrice A; P ≤ 0.0137, Dentifrice B).